2020
DOI: 10.1038/s41598-020-62913-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell colony growth by contact inhibition

Abstract: Contact inhibition is a cell property that limits the migration and proliferation of cells in crowded environments. However, its role in the emergence of the collective behaviors observed experimentally is not clear. Here we investigate the growth dynamics of a cell colony composed of migrating and proliferating cells on a substrate using a minimal model that incorporates the mechanisms of contact inhibition of locomotion and proliferation. We find two distinct regimes. At early times, when contact inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…Given that cell density appears to affect vortex formation and is known to control contact inhibition of locomotion and proliferation ( Schnyder et al, 2020 ), we explored the spatiotemporal evolution of cell density. Constructing average kymographs in the same way as for speed, radial velocity, and vorticity, we observe that the vortex region in the center of small tissues is accompanied by an unexpected local density minimum ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that cell density appears to affect vortex formation and is known to control contact inhibition of locomotion and proliferation ( Schnyder et al, 2020 ), we explored the spatiotemporal evolution of cell density. Constructing average kymographs in the same way as for speed, radial velocity, and vorticity, we observe that the vortex region in the center of small tissues is accompanied by an unexpected local density minimum ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical forces are especially important for normal epithelial homeostasis, and they are often altered in diseases such as cancer, where cellular contractility is modified, and higher compressive forces rise from the confined growth of the tumor 20 , 21 . Furthermore, intercellular contact-induced arrest of cell growth underlies the homeostatic control of cell growth, density, and tissue/organ size 7 , 22 . In recent years, studies on mechanical stretching have been uncovering the cellular responses to strain 23 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The acquired data from the biochemical analyses further indicated that compression induced cleavage of YAP1 but did not affect YAP1 phosphorylation at S127P. Cytoplasmic retention of YAP is associated with suppression of nuclear YAP activity and increased contact inhibition and Hippo signaling 32,63 . Importantly, compression promoted the expression of full-length catenin together with higher molecular weight fractions suggestive of β-catenin membraneassociation and inhibition of β-catenin -mediated growth signaling.…”
Section: Thus These Experiments Indicate That the Concept Can Be Used In Mechanobiological Researchmentioning
confidence: 92%
“…Mechanical forces are especially important for normal epithelial homeostasis and they are often altered in diseases such as cancer, where cellular contractility is modified, and higher compressive forces rise from the confined growth of the tumor [28][29][30][31] . Furthermore, intercellular contact-induced arrest of cell growth and contact inhibition underlies the homeostatic control of cell growth, density and tissue/organ size 14,32 .…”
Section: Introductionmentioning
confidence: 99%